Investigating the IMF cone angle control of Pc3‐4 pulsations observed on the ground. Issue 3 (18th March 2014) - Bier, Elianna A.; Owusu, Nana; Engebretson, Mark J.; Posch, Jennifer L.; Lessard, Marc R.; Pilipenko, Viacheslav A.
Abstract Many studies have shown that Pc3‐4 pulsations (~0.014–0.1 Hz) observed in Earth's magnetosphere during daytime hours originate in the ion foreshock region of the solar wind, just upstream from Earth's bow shock. They occur when the interplanetary magnetic field (IMF) is primarily radial—when the IMF cone angle θxB ≤ 45°. However, our knowledge of ion foreshock conditions is often incomplete because of the very limited number of spacecraft providing upstream data. In this study we compared 13 months of wave observations at two widely separated ground stations (Hornsund, Svalbard and Halley, Antarctica) to IMF values in the OMNI database in order to test this relation. Values of θxB and the empirically predicted wave frequency (fcalc = 0.06 BIMF) were compared to daily Fourier spectrograms displaying pulsation power and frequency. Although there was often good temporal agreement between low θxB and increased Pc3‐4 wave power, numerous counterexamples were also evident. A statistical study of wave activity in quarter hour increments showed that Pc3‐4 pulsations were associated with low θxB values, 81% of the time at Hornsund and 83% at Halley. IMF cone angle data from all available upstream monitors were compared to wave observations for a more limited number of days; many of these showed inconsistent IMF orientations. This study indicates some of the limitations of the existing upstream monitors and provides a quantitative estimate (~80%) of the accuracy of the OMNI data set in characterizing conditions near the nose of Earth's bow shock under predominantly radial IMF conditions.